Morocco - Mind the Gap : Empowering Women for a More Open, Inclusive and Prosperous Society - World Bank Group (World Bank, Washington, DC, 2016)
This report is about women in Morocco who continue to face obstacles in social, economic, and political participation. These obstacles are a result of discriminatory legislative frameworks, social norms that restrict legal rights, and limited economic participation. Women’s economic participation in Morocco was at 26 percent which is among the lowest in the world, and has not changed since 1990. The ultimate objective is to promote women’s empowerment as a means to achieve a more inclusive, open, and prosperous society. This report is arranged as follows :(a) chapter one will present the progress thus far and the remaining important challenges for women in Morocco.; (b) chapters two and three focus on economic empowerment and employment outcomes and on the remaining legislative and or social discrimination that continue to restrict women agency in chapter four; and (c) chapter five will conclude by presenting some key areas of strategic intervention for the government and other development actors which are not only of greater potential impact but also a prerequisite for women’s agency and empowerment. The main findings in the report are as follows: (i) unequal access to education and resources continue to hinder women’s human development progress; (ii) gender segregation in terms of employment is pervasive, with women mostly working in low productivity sectors; (iii) demographic factors and social norms also affect women’s decisions to join the labor force; (iv) only fifteen percent of women in urban areas are employed, against sixty two percent of men, and this gap has remained virtually unchanged in the past; (vi) there is a substantial wage gap between men and women, even when controlling for education and professions; and (vii) traditional explanations for Female Labor Force Participation (FLFP) long-term trends account only partially for Morocco’s observed outcomes. Agency has a role, often a strong one, in contributing to women’s human development and economic opportunities, and opening opportunities for greater participation in social and political life. Despite important reforms, gaps remain in the legal framework, negatively impacting economic, social, and political development for women. The main conclusions and recommendations are follows: (a) much has been done but much remains to be done to improve women’s access to economic opportunities and individual empowerment; (b) women can actively contribute to Morocco’s economic growth only if the remaining barriers that still prevent women from working in high productivity sectors are removed; (c) removing regulatory barriers and easing the access to credit for female entrepreneurs is key to creating more jobs; (d) further reforms of the Labor code could be designed taking into account specific obstacles to women’s economic participation; (e) government action to level the playing field across the lifecycle would strengthen women’s opportunities and ultimately socio-economic outcomes; (f) the Goverment of Morocco (GoM) has taken considerable steps in closing gender equality gaps in law, but action is needed to ensure consistency throughout legislative frameworks; and (g) mainstreaming gender into policy action is key to achieving gender equality and women empowerment.